Exploration of cytotoxic and genotoxic endpoints following sub-chronic oral exposure to titanium dioxide nanoparticles. (September 2019) - Chakrabarti, Srijita; Goyary, Danswrang; Karmakar, Sanjeev; Chattopadhyay, Pronobesh
Health hazards of titanium dioxide nanoparticles (TiO2 -NPs) have raised severe concerns because of the paucity of information regarding the toxic effects among the population. In the present research, the in vitro and in vivo cytotoxic potential of TiO2 -NPs were evaluated using flow cytometric techniques. Further, in vitro and in vivo genotoxic endpoints were estimated by means of comet, micronucleus (MN), and chromosomal aberration (CA) assays. In vitro analysis was performed at the concentration range of 10–100 µg/mL using murine RAW 264.7 cells. In vivo experiments were conducted on Albino mice (M/F) by exposing them to 200 and 500 mg/kg TiO2 -NPs for 90 days. Decreased percentage of cell viability with higher doses of TiO2 -NPs was evident in both in vitro and in vivo flow cytometric analysis. Further, an impaired cell cycle (G0 /G1, S, and G2 /M) was reflected in the present investigation following the exposure to TiO2 -NPs. Increased comet scores such as tail length, % DNA in tail, tail moment, and olive moment were also observed with the higher doses of TiO2 -NPs in vitro and in vivo comet assays. Finally, the in vivo MN and CA assays revealed the formation of MN and chromosomal breakage following the exposure to TiO2 -NPs.